TAX INCENTIVES IN FOREIGN DIRECT INVESTMENT IN CHINA AND THE IMPACT OF CHINAS NEW ENTERPRISES INCOME TAX LAW 2008 - ZHANG, Xi yao (2008)
The Promulgation of Chinas new EIT Law 2008 has attracted major concern world widely. It is a milestone in Chinas economic development history. Far before the promulgation, many researches have been conducted to estimate the possible impact of new EIT Law on both Domestic and Foreign Direct Investment Enterprises. This paper first reviews Chinas FDI development during the last few decades and the role of tax incentives played during this period, followed by an overview of Chinas major fiscal reforms. It then introduces major principle EIT Law and examines possible impacts of the new law on FIEs operating in labour intensive industries based on a case study and gives possible solution and suggestions.